Fire fighters and police repond to a rubbish fire at 29 Auburn Street, December 4, 1952 - Boston Housing Authority (Tufts Archival Research Center, 2005)
Street-level view of Auburn Street looking south from 44 Auburn Street. Several buildings, both commercial and residential, line Auburn Street. A grocery store is located on the left-side of the photograph at 238 Chambers Street. Two fire trucks are pictured in the photograph. One is parked at the intersection of Chambers and Auburn Streets, and the second is parked along the sidewalk opposite of 29 Auburn Street. A police car is parked in front of one of the fire trucks. Other automobiles and trucks are parked along the street, and several pedestrians, including small children, are included in the photograph. A policeman is seen walking beside one of the fire trucks. A line crosses out the Boston Housing Authority stamp and above it is written: Cancelled 12/1962, on the back of the photograph. 8 x 10 Photographs